Азбука песен: [сборник] / Ю. С. Энтин ; художник О. Ю. Горбушин - Энтин Юрий Сергеевич (Наши любимые мультфильмы, 2007)
Экземпляры: ДБ (20070911) / Инвентарный номер: 38851 / Цена: 49.40 / Авт.знак: Э 67 / ББК: 84(2Рос=Рус)6